2018
DOI: 10.1590/0103-8478cr20170775
|View full text |Cite
|
Sign up to set email alerts
|

Short food supply chain: characteristics of a family farm

Abstract: Short Food Supply Chains (SFSCs) provide a dependable substitute for conventional supply chains, as their food reflects the characteristics of “local”, “natural”, “healthy” and “reliable”. For the family farmer, the short chains constitute anexcellent way of diversifying their produce, gaining higher added value and thus warranting steadier revenues. This paper thus aims to discern the distinguishing features that the short chains offer, in general, to the family farm. To accomplish this, a literature review w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 10 publications
3
29
1
6
Order By: Relevance
“…Short food chains (SFSCs) have increasing popularity nowadays [9]; however, their role in the food trade of developed countries is limited [10]. They are unable to "replace" the global food systems in the lives of consumers [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Short food chains (SFSCs) have increasing popularity nowadays [9]; however, their role in the food trade of developed countries is limited [10]. They are unable to "replace" the global food systems in the lives of consumers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…They are unable to "replace" the global food systems in the lives of consumers [11,12]. They have the potential of supporting local and regional development and contributing to food quality for consumers [9] and job creation [13]. There are indications in the literature that these chains are capable of contributing to sustainability, due to their particular characteristics and small scale, although some aspects that are considered to be beneficial are also disputed by the experts' opinions [14].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that all these food items purchased by 91.6% of the municipalities were bought from local producers (of the same municipality) showing short supply chains. Studies showed that this system promotes an increase in socioeconomic factors through the creation of new jobs and development of the local market for food production which boost the economy (AGUIAR et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the institutional purchase of family farming was facilitated and the procedures of this process were simplified through a Public Call (BRASIL, 2009;BRASIL, 2015). Acquisition of products from family farming has become part of a policy that recognizes the need to produce food that meets the nutritional demands of the population and also guarantees the economic and social growth of the family producer including the creation of short production and marketing chains (AGUIAR et al, 2018). Such policy brings the producer and the consumer close to one another, strengthens social relationships, and values productive diversity (BRASIL, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…One of the driving forces of the environmental sustainability of urban food production is the concept of a local food system, as demonstrated by several authors [35,36].…”
Section: Environmental Sustainabilitymentioning
confidence: 99%